Объекты государственной собственности - Manzula, Yulia (Przegląd Prawniczy Uniwersytetu im. Adam Mickiewicza, 2015)
The study aims at an evaluation of the state property right in the context of its object. The author analyse the features of the state property right according to the object it is related to.